Islamic Legal Philosophy as Epistemological Foundation for Interdisciplinary Integration of Science, Society, and Sharia in Modern Muslim Communities - Afif Syafiuddin; Marsatana Tartila Tristy (International Forum of Researchers and Lecturers, 2025)
This study explores the integration of Islamic legal philosophy with modern knowledge systems, focusing on the potential for bridging science, society, and Sharia. Islamic legal thought, deeply rooted in divine revelation and human reason, provides a comprehensive epistemological foundation that unifies knowledge across scientific, social, and religious domains. The research examines key principles such as maqāṣid al-sharīʿah (the higher objectives of Islamic law), which aim to preserve essential aspects of life, including intellect, religion, and property, ensuring that scientific advancements align with Islamic moral values. Through philosophical analysis, the study highlights how Islamic legal philosophy can address contemporary challenges by fostering a balanced approach that incorporates ethical guidelines into various fields, such as public policy, healthcare, and technology development. The integration of Sharia-based ethics into scientific research is shown to promote justice, equity, and the common good. The study also discusses the implications for Muslim-majority societies, proposing the integration of Islamic legal principles into education systems to develop ethically responsible professionals. Additionally, the challenges of reconciling modern scientific progress with traditional religious values are acknowledged, with recommendations for further research to refine interdisciplinary models. The findings underscore the importance of interdisciplinary collaboration between Islamic jurisprudence, social sciences, and natural sciences, offering valuable insights into addressing global challenges through an Islamic ethical framework. This study ultimately advocates for a holistic approach to knowledge development that balances modernity with religious traditions.